Ultrasonographic evaluation of the distal femoral and talar cartilage thicknesses in patients with poliomyelitis: a cross-sectional observational study - Angerová, Yvona; Mezian, Kamal; Kara, Murat; Pudilová, Veronika; Sobotová, Karolína; Michalčinová, Klaudia; Konopáčová, Eva; Özçakar, Levent (European journal of physical and rehabilitation medicine, 2020)
BACKGROUND: Sequelae of poliomyelitis, coupled with asymmetric impairment and weight-bearing, typically alter walking biomechanics which can be associated with the knee and ankle osteoarthritis. AIM: We aimed to investigate whether the distal femoral and talar cartilage thicknesses were different in patients with poliomyelitis. DESIGN: Cross-sectional observational study. SETTING: Outpatients, tertiary care center. POPULATION: Thirty-six patients (12 males, 24 females) with a history of poliomyelitis and 36 age, gender and body mass index similar healthy subjects (11 males, 25 females) were enrolled. Mean values for age, body mass index and age of the poliomyelitis onset were 70.2±4.6 years, 27.2±5.7 kg/m2, and 3.6±2.4 years. METHODS: Visual Analogue Scale (VAS) was used to assess pain. Lower limb muscle strengths were measured by manual muscle testing. The more affected side was identified according to the lower limb manual muscle testing. Bilateral distal femoral cartilage from the lateral femoral condyle, intercondylar area, medial femoral condyle and talar cartilage thicknesses were measured using ultrasound imaging. RESULTS: Among patients, the onset of poliomyelitis was at 3.6±2.4 years of age, and Functional Ambulation Category scores were 5 (3-5). VAS scores were similar between the sides affected more and less by poliomyelitis. All cartilage thicknesses (except the talar cartilage) of the patients were found to be thinner on the more affected side than the less affected side (all P<0.001). The thickness of talar cartilage was thinner compared to control subjects (P<0.001). Among the patients, quadriceps muscle strength was positively correlated with medial condyle (r=0.377, P=0.024), intercondylar area (r=0.399, P=0.016) and lateral condyle (r=0.363, P=0.030) thicknesses. Knee VAS scores were negatively correlated with talar cartilage thicknesses (r=-0.393, P=0.018). CONCLUSIONS: We found a thinning of the distal femoral condyle in the more affected paretic sides of poliomyelitis patients as compared to both those of less affected sides and those of healthy controls. Talar cartilages on both sides of the patients were thinner compared to control subjects. CLINICAL REHABILITATION IMPACT: Our preliminary findings may contribute to the long-term management of patients with long-term poliomyelitis sequelae.
Keywords: senioři; svalová síla; Femur; Poliomyelitis; poliomyelitida; Cross-Sectional Studies; Knee Joint; talus; mužské pohlaví; Talus; hlezenní kloub; průřezové studie; Pain Measurement; měření bolesti; kloubní chrupavka; Muscle Strength; ultrasonografie; ženské pohlaví; Humans; kolenní kloub; Ankle Joint; Ultrasonography; femur; Female; Aged; Cartilage, Articular; lidé; Male